Recent advances in flame retardant polymers via thiol-ene click chemistry - ÇAKMAKÇI, EMRAH (My University, 2023)
Within the toolbox of click chemistry, the utilization of thiol-ene reactions for polymer synthesis and modification is a current area of intense attention. Thiol-ene click reactions are used for a broad range of applications. One main area that needs particular attention, where thiol-ene click reactions are immensely employed, is the fabrication of coatings. Especially, when light is used to trigger the thiol-ene reactions, coatings can be prepared within seconds. This method is known as thiol-ene photopolymerization (TEP) and it is a marvelous advancement among light-induced crosslinking systems. TEP is a powerful tool for the preparation of coatings. The synthesis of phosphorous monomers for TEP has prominent importance for improved thermal properties and flame retardancy. Here, the existing literature on flame retardant TEP systems and reactive phosphorous monomers used in TEP are summarized. This review mainly highlights the studies on thermosets yet some linear polymer examples are also included. While this mini-review focuses mostly on TEP, relevant works involving other thiol-ene polymerization routes (i.e. thermal thiol-ene polymerization) rather than photopolymerization are presented. Finally, studies that utilize thiol-ene click reactions to synthesize phosphorous monomers and flame retardants are also given.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; MALZEME BİLİMİ, SERAMİK; POLİMER BİLİMİ; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; MATERIALS SCIENCE, CERAMICS; POLYMER SCIENCE; MATERIALS SCIENCE, MULTIDISCIPLINARY; Seramik ve Kompozitler; Fizik Bilimleri; Genel Kimya; Polimerler ve Plastikler; Malzeme Kimyası; Ceramics and Composites; Physical Sciences; General Chemistry; Polymers and Plastics; Materials Chemistry; flame retardant; nitrogen; phosphorus; Thiol-ene click; thiol-ene photopolymerization